Murphy [Andrew Peacock, John Howard, Ian Sinclair] - Pryor, Geoff, 1944- (1984)
Despite the reluctance of the Federal Coalition to use Parliament to name the High Court judge mentioned in the NSW police surveillance tapes later published in the Age newspaper (as 'the Age tapes'), Mr Lane, Minister for Transport in the Queensland National Party Government has no such qualms and cheerfully names Justice Lionel Murphy in State parliament.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 7 March 1984.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Sinclair, Ian McCahon, -- 1929- -- Caricatures and cartoons; Howard, John, -- 1939- -- Caricatures and cartoons; Peacock, Andrew, -- 1939-2021 -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Federal politicians